Slinky malinky, open the door - Dodd, Lynley (London : Puffin, 1995)
Slinky Malinky a mischievous cat, and stickybeak Syd, a bird get into lots of trouble when they are left alone in the house.
Keywords: Birds -- Fiction; Cats -- Fiction